Monitoring and Evaluating Social and Emotional Learning - Kimberly Schonert-Reichl; Jennifer Kitil; Julie Sauve; Jessica Trach (Unesco, 2022)
As conveyed in the widely known axiom ‘What gets assessed gets addressed’ – we now know that assessing and monitoring social and emotional learning is critical for creating accountability systems in which priority is given to the promotion of students’ social and emotional competencies and skills. The present chapter introduces the rationale for evaluating and monitoring students’ social and emotional competencies in schools, and delineates the benefits of an SEL monitoring approach. Also presented are several examples of ways to specifically evaluate SEL programmes, which is followed by examples of a public health approach to monitoring children’s social and emotional competence at the population level. The chapter ends with a comprehensive list of examples of SEL assessments that: (a) measure students’ intrapersonal and/or interpersonal competencies, (b) were developed for pre-kindergarten to Grade 12 students, (c) are actively used in practice and not just for research purposes, (d) are strengths-based (assess strengths rather than deficiencies), and (e) have evidence of sound psychometric properties.
Rethinking Learning: A Review of Social and Emotional Learning for Education Systems